Propuesta de formación para la optimización del talento humano en una empresa constructora (2023)
This training proposal for the optimization of human talent in an MSME in the construction sector arose from the need to propose some organizational management strategies related to business competitiveness and the way in which human talent influences this aspect. . According to this, the main objective of the document focused on generating a training proposal in personnel management for the optimization of human talent in an MSME construction company by addressing elements such as organization management, development management and assessment, For its scope, it began with the identification of the main characteristics of human talent that an MSME company in Colombia must have through a documentary review, giving way to the description of the characteristics in personnel management that it is intended to generate in the workers of an MSME in the construction sector, ending with the design of the training program. The methodology according to the qualitative, descriptive and interpretive approach. The results reflected that companies should focus special attention on design management, development management and valuation. It is concluded that the development of competencies is fundamental for business management and organization, business innovation and leadership. In the face of quality in the product or service, it is necessary to deepen attention and comprehensive service and, with respect to productivity, it is essential to address efficiency. .